An approximation property of Gaussian functions - Soon-Mo Jung; Hamdullah Sevli; Sebaheddin Sevgin (Electronic Journal of Differential Equations, 2013)
Using the power series method, we solve the inhomogeneous linear first order differential equation $$ y'(x) + lambda (x-mu) y(x) = sum_{m=0}^infty a_m (x-mu)^m, $$ and prove an approximation property of Gaussian functions.